Neonatal gastric perforation: is prematurity the only cause? - Dash, Manas R.; Barma, S. K.; Panigrahi, Pranay; Parida, P.; Mohanty, P. K.; Jena, P. K. (International Journal of Advances in Medicine, 2020)
Background: Neonatal Gastric Perforation (NGP) is a serious and life-threatening emergency and challenging in terms of diagnosis and management. The precise aetiology remains obscure in most cases. Published literatures provide theories of gastric ischemia, aerophagia & trauma with or without definite inciting pathology. Owing to its high mortality rate, it requires early detection & urgent intervention to bring out the newborn from this catastrophe. Methods: We report five cases of neonatal gastric perforation over period of 2013-2019 admitted to a tertiary paediatric surgical care hospital managed by early detection, prompt resuscitation along with exploration and primary repair of the defect in gastric wall. Results: The common feature in these five cases were preterm age, low birth weight, hypoxic event and marked abdominal distension causing respiratory distress. Features of imminent or complete septic shock were present in all cases. Perforation was found on anterior wall along greater curvature of stomach in all babies. Four babies out of five survived except in one case of jejunoileal Artesia that developed gastric perforation in post operative period. Conclusions: Neonatal gastric perforation should be suspected in cases of rapidly deteriorating premature newborn with gross abdominal distension and pneumoperitoneum. In our opinion, etiology of NGP is multifactorial. Prematurity, low APGAR score with vigorous resuscitation could be a clue for early diagnosis. Good outcome in our series was due to early diagnosis and prompt pre and postoperative measures. Additionally, sterile gastric content in peritoneum might lead to survival from this catastrophic event.